Specific gravity and morphological characteristic of Sentang (Azadiracta Excelsa) wood / Nik Hairul Badri Daud, Nur Aisyah Hanzah and Zainab Awang - Daud, Nik Hairul Badri; Hanzah, Nur Aisyah; Awang, Zainab (2009)
The studies of specific gravity and morphological characteristic of Sentang (Azadirachta Excelsa) wood were determined using the water displacement method and based on the TAPPl standard respectively. The specimens used from three different parts of the tree that is, from Diameter Breast High (DBH), Bottom and Top. The studies showed the differentiation of Specific Gravity and Morphological Characteristic at different high level. From the result of the study we will know whether this species can be use in wood industry to produce a good quality product.